Search for a new society : tribal theology for North East India - Tribal Theology for North East India (Seminar) (2010 : Gauhati, India); Vashum, Yangkahao; Haokip, Peter; Pereira, Melville; North-Eastern Social Research Centre (Gauhati, India); Eastern Theological College (Jorhāt, India) (Guwahati, Assam NESRC, 2010)
Contributed articles presented at the seminar titled "Tribal Theology for North East India", held at Gauhati, during April 27-29, 2010; organized by North-Eastern Social Research Centre, in collaboration with Eastern Theological College, Jorhat.
Includes bibliographical references and indexes.
Keywords: Theology, Doctrinal -- India, Northeastern -- Congresses; Christianity -- India, Northeastern -- Congresses; India, Northeastern -- Scheduled tribes -- Religion -- Congresses